Features of rotational modes of vibrations of water molecules in free and bound states - Малафаев, Николай Тимофеевич; Погожих, Николай Иванович; Иштван, Егор Алексеевич (Eastern-European Journal of Enterprise Technologies, 2013)
The paper considers rotational (including librational - dimensional rotational) vibrations and the number of corresponding vibrational modes for molecules of water in its various physical phase states - liquid, ice and "bound". The main purpose of the research is comparative analysis of vibrational modes of molecules of water in different phase states, taking into account the results of previous paper [6] on vibrational modes of molecules in liquid water. The analysis of changes in the number of rotational modes of molecules of water for its various phase states and physical consequences of these changes for physical and thermal properties of water was conducted. Increased force of hydrogen bonds of water molecules in ice or bound ice-like state leads to reducing the number of rotational vibration modes, and accordingly, the number of degrees of freedom of molecules and heat capacity of the phase. State, mobility and structure of macromolecules in aqueous solutions are determined by the strength of ice-like "skeleton/corset" of their hydration shell formed by "bound" water molecules.